2019
DOI: 10.3390/plants8060147
|View full text |Cite
|
Sign up to set email alerts
|

Role of Silicon in Mediating Salt Tolerance in Plants: A Review

Abstract: Salt stress is a major threat for plant growth worldwide. The regulatory mechanisms of silicon in alleviating salt stress have been widely studied using physiological, molecular genetics, and genomic approaches. Recently, progresses have been made in elucidating the alleviative effects of silicon in salt-induced osmotic stress, Na toxicity, and oxidative stress. In this review, we highlight recent development on the impact of silicon application on salt stress responses. Emphasis will be given to the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(109 citation statements)
references
References 116 publications
(208 reference statements)
2
107
0
Order By: Relevance
“…Moreover, EcLsi2 and EcLsi3 might have evolved from EcLsi1 and/or EcLsi6 and/or from both genes due to a duplication event during evolution. The phylogenetic analysis of silicon transporter genes was found to be useful to establish the evolutionary relatedness and divergence in different plant species 32,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EcLsi2 and EcLsi3 might have evolved from EcLsi1 and/or EcLsi6 and/or from both genes due to a duplication event during evolution. The phylogenetic analysis of silicon transporter genes was found to be useful to establish the evolutionary relatedness and divergence in different plant species 32,39 .…”
Section: Discussionmentioning
confidence: 99%
“…The plant organs, such as leaf and root, orchestrate defense mechanisms (internal or external) in response to abiotic stress [9][10][11]. Root is the first organ exposed to water stress because water stress results from an insufficient or excessive level of water in the soil [7,8,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that Dof transcription factors are involved in regulation of biotic and abiotic stress response [20,21]. For example, the action of SlCDF1 and SlCDF3, two Dof transcription factors in tomato, caused improved drought and salt stress tolerance in transgenic plants [22]; and CDF3, a cycling DOF factor in Arabidopsis, promoted drought, cold, and osmotic stress tolerance [23].Crops are challenged by many types and levels of stresses such as salt and drought [24,25]. As one of the world's most important staple crops, wheat (Triticum aestivum L.) is affected by various kinds of stress that limits the achievement of yield potential [26].…”
mentioning
confidence: 99%
“…Crops are challenged by many types and levels of stresses such as salt and drought [24,25]. As one of the world's most important staple crops, wheat (Triticum aestivum L.) is affected by various kinds of stress that limits the achievement of yield potential [26].…”
mentioning
confidence: 99%